(untitled) (Dermatology Reports, 2022)
Our case-control study of 60 patients with psoriasis vulgaris (PsV), 20 patients with psoriatic arthritis (PsA), and 34 healthy control participants in Ho Chi Minh City Hospital of Dermato-Venereology from October 2019 to September 2020 aimed to evaluate the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and associated factors in patients with PsV and PsA. Results showed that in the PsV group, significant correlations of NLR with Psoriasis Area and Severity Index and the high-sensitivity C-reactive protein (hs-CRP) level was noted (r=0.374 and r=0.352, respectively; P=0.003 and P=0.006, respectively). NLR was also related to PsA (P=0.007, OR=1.57). The area under the curve (AUC) for NLR in predicting PsA was 0.7554 (cut-off, 2.239; sensitivity, 85%; specificity, 61.67%). PLR was also related to PsA (P=0.008, OR=1.01). The AUC for PLR was 0.6513 (cut-off, 159.6; sensitivity, 55%; specificity, 88.33%). Thus, complete blood count parameters can reflect the inflammatory status of patients with PsV and PsA. NLR and PLR may be potential diagnostic markers for PsA in patients with psoriasis. Future studies should aim to assess the value and usage of these parameters.